Assessment of school physical education learning - Hein Mendes, Evandra (2020)
This study analyzed the characteristics and outlines of the assessment process of school physical education learning. To this end, forty-six physical education coaches in the Paraná public school system completed a semi-structured questionnaire with open questions about the student assessment process. Data revealed that coaches assessed the cognitive, physical-kinesthetic, and socio-affective skills of students, using the following criteria: retention of information, understanding and application of concepts, individual evolution, physical/technical performance, cooperation, participation and behavior, through theoretical tests, assignments, and observations.